2016
DOI: 10.1002/jmri.25378
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and reproducibility assessment of the regional brain T2 relaxation in naïve rats at 7T

Abstract: 1 J. Magn. Reson. Imaging 2017;45:700-709.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Altogether, reported values are in good agreement with several recent studies (Del Bigio et al, 2011, Gigliucci et al, 2014, Koundal et al, 2015, Liachenko and Ramu, 2017, Suleymanova et al, 2014. In conclusion, we have demonstrated the feasibility of multicenter preclinical studies, sharing raw data and processing pipelines between distributed centers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Altogether, reported values are in good agreement with several recent studies (Del Bigio et al, 2011, Gigliucci et al, 2014, Koundal et al, 2015, Liachenko and Ramu, 2017, Suleymanova et al, 2014. In conclusion, we have demonstrated the feasibility of multicenter preclinical studies, sharing raw data and processing pipelines between distributed centers.…”
Section: Discussionsupporting
confidence: 91%
“…They show that T1 relaxation time increases with magnetic field while T2 relaxation time decreases (de Graaf et al, 2006, Wright et al, 2008, van de Ven et al, 2007. Some values have been reported in the literature for few brain regions (Barbier et al, 2005, Behroozi et al, 2018, Cremillieux et al, 1998, Del Bigio et al, 2011, Gigliucci et al, 2014, Koundal et al, 2015, Liachenko and Ramu, 2017, Suleymanova et al, 2014, but no consensus has been reached yet about values of reference for specific rat brain regions. To define such reference maps, a large number of brain structures or regions should be considered and a sufficient number of animals should be included to reflect inter-individual variability.…”
Section: Discussionmentioning
confidence: 99%
“…In the present 7T study, we have used a CPMG sequence with 10.73‐ms interpulse interval. Studies in humans and animals have reported that T 2 values measured in brain tissue using CPMG sequences are dependent on the refocusing interval due to dynamic dephasing caused by the strong magnetic field gradients created by deoxygenated blood in veins and eventual iron/ferritin deposits. Therefore, it is important to keep in mind that the T 2 values reported in the present study correspond to the so‐called apparent T 2 , as defined in .…”
Section: Discussionmentioning
confidence: 99%
“…They show that T1 relaxation time increases with magnetic field while T2 relaxation time decreases (de Graaf et al, 2006;van de Ven et al, 2007;Wright et al, 2008). Some studies also reported regional values (Cremillieux et al, 1998;Barbier et al, 2005;Del Bigio et al, 2011;Gigliucci et al, 2014;Suleymanova et al, 2014;Koundal et al, 2015;Liachenko and Ramu, 2017;Behroozi et al, 2018), but no consensus has been reached yet about values of reference for specific rat brain regions. To define such reference maps, a large number of brain structures or regions should be considered and a sufficient number of animals should be included to reflect inter-individual variability.…”
Section: Introductionmentioning
confidence: 99%